THE POSSIBILITY OF USING TIMBER FROM PLANTATION FOREST TREATED WITH PLASTIC AND CCB FOR MARINE CONSTRUCTION - Mohammad Muslich; Nurwati Hadjib (Indonesian Journal of Forestry Research, 2008)
Recently, timber  estate or plantation forest plays an important role on wooden based industries.  However, the  plantation timber  quality is relatively low.  Some treatments  have been developed to improve  its low quality, such as preservation with CCB (Chromate Copper Boron) and impregnation with plastic compounds. This study is to compare the durability of timber treated with  plastic and CCB,  non-treated from plantation forest timber  as well  as from natural  forest. The plantation timber  studied were  jeungjing  (Paraserianthes falcataria), damar  (Agathis sp.), pinus  (Pinus merkusii), and rubberwood (Hevea brasilliensis). Non-treated timbers that usually used for marine construction were ulin (Eusideroxylon zwageri), jati/teak  (Tectona grandis), laban (Vitex pubescens) and merbau  (Instia bijuga). After  6 and 12 months,  the results showed that CCB  preserved  timber  were  more durable  than plastic  impregnated timber  and non- treated timber. Wood samples were mostly attacked by marine borer organisms from the family of  Pholadidae  and Teredinidae. The experiment results revealed the possibility of using those plantation forest timber species for marine construction purposes.